Ultra-thin enzymatic liquid membrane for CO2 separation and capture - Yaqin Fu (Nature Portfolio, 2018)
Porous membranes show great promise for CO2 separation and capture, but are currently limited by a trade-off between permeance and selectivity. Here, the authors fabricate a bio-inspired, ultra-thin enzymatic liquid membrane that displays exceptional CO2 permeability and selectivity under ambient conditions.